The Effect of Service Quality and Customer Relationship Management Towards Customer Loyalty: (Case Study on Customer GTT Café Mojokerto) - Lorenzo Yauwerissa; Jushua Sutanto Putra (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
This study aims to determine the effect of service quality and customer relationship management on customer loyalty at GTT Café Mojokerto. The population used is all consumers of GTT Café Mojokerto who have visited more than once, while the sample set by the researcher is 124 consumers who have visited at least twice. Data collection techniques in this study were taken by distributing questionnaires to customers who were there and measured based on a Likert scale. The variables used are service quality and customer relationship management as independent variables and customer loyalty as the dependent variable. Furthermore, the researcher processed the data using the SPSS 25 program to obtain significant results in the study. Based on the results of the research analysis, it is obtained the hypothesis that service quality has an effect on customer loyalty and customer relationship management has an effect on customer loyalty and the two variables simultaneously influence customer loyalty so that it can be said that all independent variables influence the dependent variable partially or simultaneously.